Kemartiran Polycarpus Mewariskan Transformasi Filosofis dan Pembentukan Moral Juga Etika Kristen - Sostenis Nggebu (STT INTI Bandung, 2025)
The importance of this article is about Polycarp's inner peace that was a support for him from the fire of man-made suffering. Terrible persecution or torment had driven him to lean more and more on Christ, his Lord, becoming the martyr of the ancient church. The purpose of the research was to explain Polycarp's attitude and stance in the face of his martyrdom. The method used in the research is a literature study. The results show that Polycarp's life lived and inherited the philosophical values of courage and steadfastness of faith. The spiritual transformation he underwent inherited the philosophical value of how true Christians deal with suffering and fit. This Apostolic Father is an example of profound character transformation and provides an ethical foundation for the next generation of Christians in facing various challenges. In conclusion, the life and faithfulness and faithfulness in Christ internalized in the life of Polycarp can be a reflection of faith for believers of all ages.